(untitled) (KULT_online, 2012)
The book Social Bioarchaeology provides 15 texts with a wide range of interdisciplinary examples of bioarchaeological research. The authors come from the United States, England, Australia, and New Zealand and present studies from all over the world as well as from different epochs. These analyses reach from early cultures of Bahrain, to Roman Italy and medieval England, and on to the colonial era in North America. Despite these different foci and methods, all successfully show new paths in social bioarchaeology.